2007
DOI: 10.1016/j.exer.2007.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule regulation of corneal fibroblast morphology and mechanical activity in 3-D culture

Abstract: The purpose of this study was to investigate the role of microtubules in regulating corneal fibroblast structure and mechanical behavior using static (3-D) and dynamic (4-D) imaging of both cells and their surrounding matrix. Human corneal fibroblasts transfected to express GFP-zyxin (to label focal adhesions) or GFP-tubulin (to label microtubules) were plated at low density inside 100 μm thick type I collagen matrices. After 24 hours, the effects of nocodazole (to depolymerize microtubules), cytochalasin D (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
7
17
2
Order By: Relevance
“…7). The decrease in the adhesion area is in agreement with results reported in previous studies [10,12]. The most likely reason for the decrease in the adhesion area is a disturbance of the mechanical balance in the cell after microtubule disruption.…”
Section: Morphological Study On Fibroblastssupporting
confidence: 82%
See 2 more Smart Citations
“…7). The decrease in the adhesion area is in agreement with results reported in previous studies [10,12]. The most likely reason for the decrease in the adhesion area is a disturbance of the mechanical balance in the cell after microtubule disruption.…”
Section: Morphological Study On Fibroblastssupporting
confidence: 82%
“…Many studies have focused on the role of the cytoskeleton in cellular mechanics [5][6][7][10][11][12], and Ingber [13] proposed a cellular mechanical model, the tensegrity model, which focused on the cytoskeletal system. This model can account for some of the mechanical behavior of living cells [7,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to lamellipodial adhesions on 2-D substrates, adhesions in 3-D matrices tended to form and treadmill in a linear pattern along individual collagen fibrils, consistent with studies showing that alignment of collagen fibrils can provide contact guidance for cell spreading and migration [55, 88–90]. Subsequent studies have used DIC imaging to evaluate the role of Rho and Rac in regulating sub-cellular mechanical activity during fibroblast spreading and migration [40, 84, 91, 92]. Such studies have demonstrated that while Rho kinase plays a central role in mediating overall force generation by fibroblasts within 3-D matrices (Fig.…”
Section: Direct Imaging Of Local Cell-induced Matrix Reorganization Isupporting
confidence: 66%
“…15,16 Rho kinases (ROCKs) were initially characterized for their roles in mediating the formation of RhoA-induced stress fibers and focal adhesions through their effects on the phosphorylation of myosin light chain. 17 In the cornea, ROCKs have been suggested to be involved in epithelial differentiation, 18 cell cycle progression, 11 cell-cell adhesion, 15 endothelial barrier integrity, 19 stromal cell phenotype conversion, 20 cytoskeleton reorganization, contractility, 21 and cell-matrix interaction. 22 Thus, we investigated the Rho-GTPase activity by PBM and found that the expression of RhoA and RhoC was significantly increased after PBM treatment.…”
Section: Discussionmentioning
confidence: 99%